Shocks and coping strategies in Sub-Saharan Africa - Scott, Douglas (2020)
This thesis comprises of three chapters. The first of these finds evidence of two distinct patterns of response to the onset of the recent drought in rural Ethiopia, indicating the existence of a poverty trap in household cattle holdings. The second chapter measures irreversible health deficits amongst young children who were exposed to the Lord’s Resistance Army insurgency in Northern Uganda. Chapter 3 estimates the short-run effect of income and expenditure shocks on household welfare in two South African townships, conditional on the method of response employed.